Survival Outcome and Prognostic Factors Among Patients With Hepatocellular Carcinoma: A Hospital-Based Study - Dinh Cong Le; Thang Minh Nguyen; Duong Hoang Nguyen; Dung Thi Nguyen; Lan Thi Mai Nguyen (Clinical Medicine Insights: Oncology, 2023)
Background: Hepatocellular carcinoma (HCC) is a leading cancer with very high incidence and mortality and low survival rate in Vietnam and worldwide. This study aimed to investigate the survival outcome and its prognostic factors among HCC patients. Methods: This is a retrospective descriptive study on patients newly diagnosed with HCC at Hanoi Oncology Hospital, Vietnam from January 2018 to December 2020. Overall survival (OS) was calculated by the Kaplan-Meier method. Log-rank test and Cox regression were used to investigate the association among patients’ OS and their diagnosis and treatment factors. Results: A total of 674 patients were included. The median OS was 10.0 months. The survival rates at 6, 12, 24, and 36 months were 57.3%, 46.6%, 34.8%, and 29.7%, respectively. The initial performance status (PS), Child-Pugh score, and Barcelona Clinic Liver Cancer (BCLC) stage at the time of diagnosis are prognostic factors of HCC OS. A total of 451 (66.8%) patients have died, most of them (375 equally 83.1%) died at home, and only 76 (16.9%) died at hospital. Hepatocellular carcinoma patients living in the rural area more likely died at home than those living in the urban area (85.9% vs 74.8%, P  = .007). Conclusions: Hepatocellular carcinoma has a poor prognosis with low OS. Performance status, Child-Pugh score, and BCLC stage were the independent prognostic factors for the survival outcome of HCC patients. The fact that most HCC patients died at home suggested that home-based hospice care needs to be paid special attention.